The nonlinear influence of harmonious information technology affordance on organisational innovation. (20th October 2020) - Chatterjee, Sutirtha; D Moody, Gregory; Lowry, Paul Benjamin; Chakraborty, Suranjan; Hardin, Andrew
Abstract: In this study, we investigate the nature of the influence of organisational information technology (IT) on innovation. To examine this relationship, we leverage a fundamental construct: harmonious IT affordance (HITA). HITA is defined as the degree of coalignment between three salient organisational IT affordances, each of which allows an organisation to carry out its most fundamental functions using IT—collaboration, maintenance of organisational memory, and management of organisational processes. We theorize that HITA has a quadratic (U‐shaped) effect on innovation. Our theory proposes that when IT affordances increasingly co‐align (reflected by increasing HITA), the organisation enters a synergistic, virtuous phase that encourages innovation. Counterintuitively, the increasing misalignment of IT affordances can also result in organisational innovation via creative dissonance, which enables organisations to look for opportunities in the presence of misalignment and leverage it to create a synergistic virtuous cycle. We conducted two empirical studies—one with high‐level IT executives knowledgeable about innovation and one with sales and business development executives (who market innovations) knowledgeable about IT—that corroborate our theory. Crucially, if the IT affordances are unrelated (low coalignment, where HITA is close to zero), then innovation does not take place. We thus surmise that the relation between HITA and innovation is quadratic.